A Framework for Near-Zero Downtime Oracle Database Upgrades and Grid Infrastructure Patching in Mission-Critical Enterprise Environments: A Production-Validated Approach - Korimilli, Sridhar Krishna (International Journal of Computational and Experimental Science and Engineering, 2025)
In this paper, a production-proven methodology of zeroing down in times during Oracle database upgrades and Grid Infrastructure patching in corporate networks is a subject of introduction. It combines DBMS_ROLLING, Transient Logical Standby and Ansible orchestration to allow upgrades and rolling patches to be carried out seamlessly. The framework was implemented on 5,000+ databases and 40+ key applications without ever affecting service availability and the cutover took less than 5 minutes. Some of the notable characteristics are real-time lag monitoring, readiness to roll off and automated validations. The solution yielded cost savings of more than 100 million and safeguarded over 850 million of the revenue stream and has shown a scalable, resilient and completely automated roadmap towards consistent availability of the Oracle system